Perbandingan Penggunaan Bahasa Jawa dan Bahasa Indonesia di Kalangan Remaja dalam Berkomunikasi di Desa Mekar Jaya, Kecamatan Baito dan Desa Lawoila, Kecamatan Konda, Kabupaten Konawe Selatan - Eka Cahya Ningsih; Ahmat Keke (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study aims to describe what factors influence the shift of Javanese language at the adolescent level in Mekar Jaya Village, Baito Subdistrict and Lawoila Village, Konda Subdistrict, South Konawe Regency and the impact of Javanese language shift on adolescents in Mekar Jaya Village. The data collection technique used ethnographic methods that are qualified by involved observation and in-depth interviews. The data analysis technique used was descriptive qualitative. The results showed that the factors that influence the shift in the use of Javanese language at the adolescent level include: (1) Family factors, namely in Mekar Jaya Village the lack of interaction and communication using Javanese in the family so that it causes children to be lazy to learn and apply Javanese in the family environment and the scope of association in the community, while in Lawoila Village Javanese language is still taught. Parents accustom their children to communicate using Javanese. (2) educational factors, although living and attending school in an environment with a majority of Javanese ethnicity, the local language used in local content subjects in elementary schools (SD) is Tolaki local language, as well as in Lawoila Village although in everyday life using Javanese but the local language taught in elementary schools is Tolaki local language. (3) Social environment factors, although living in an environment where the community is of Javanese ethnicity, the language actively used by the community to communicate is Indonesian, unlike in Lawoila Village which still uses Javanese in the social environment and youth association. From the occurrence of Javanese language shift, the impact is that Indonesian is easily understood by ethnicities other than Java, meaning that Indonesian can make it easier for Javanese people to communicate with people in the neighborhood where they live.